Persicaria chinensis (Linnaeus) H. Gross var. Hispida (Hooker f.) Kantachot (Polygonaceae): A New Distributional Record for West Bengal, India - Paul, Payel; Chowdhury, Monoranjan (Asian Journal of Biological and Life Sciences)
Present work spotted a small bushy habitat of, Persicaria chinensis (Linnaeus) H. Gross var. hispida (Hooker f.) Kantachot, a less known member of family Polygonaceae A. Jussieu on the hilly slops at Kalimpong of Darjeeling Himalaya of West Bengal. This weak annual herb is quite rare and recorded from its extended geographical area outside the Meghalaya and Nagaland of India and first time enlisted for the flora of West Bengal. The taxonomic features, ecological notes and photographs of the species are provided.
Keywords: Distribution; New record; Persicaria chinensis (Linnaeus) H. Gross var. hispida (Hooker f.) Kantachot; West Bengal